PENGARUH PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE I PHONE DI BATAM - Rosmeili, Rosmeili; Pranoto, Suryo Budi (SCIENTIA JOURNAL, 2019)
Changes in the environment constantly rolling in the process of development of a State, either directly or indirectly affect the life of the economy and society. In a highly competitive globalization, every organization will try to survive. Companies are faced with such complex circumstances and are required to be able to determine a strategy as a tool to deal with the situation. One step is to run an effective and efficient marketing concept. The purpose of this research is there is influence between product, price, promotion and distribution channel to decision of purchasing mobile phone Iphone dibatam in this research is all population which is used is consumer who buy mobile phone Iphone in Town batam. The retrieval technique used is Likert scale. The samples taken based on the above formula is 400 people. Analyzer used is doubled linear regression with first tested with validity test and reliability. The result of this research is product, promotion price and distribution channel to decision of purchasing mobile phone in batam.